Parent-child interactions and adaptive behavior in children with Down syndrome - Howshar, Mackenzie, author; Fidler, Deborah, advisor; Hepburn, Susan, committee member; Knight, Andrew, committee member (Colorado State University. Libraries, 2018)
Adaptive behavior is essential for the development of independence in individuals with developmental disabilities. Individuals with higher levels of adaptive behavior tend to require less support from caregivers than those with lower levels of adaptive behavior. The current study examined the association between parenting behavior and child adaptive behavior within the context of a parent-child interaction in dyads with and without a child diagnosis of Down syndrome (DS). Findings showed parents of children with DS engaged in significantly more directives than parents of TD children. Additionally, there was a significant negative association between parent directives at Time 1 and child adaptive behavior at Time 2 overall, whereas there was a significant positive association between parent teaching at Time 1 and child adaptive behavior at Time 2 in the DS group. Findings from this study may be useful for informing future parenting interventions.